Protective effect of cysteine—HCl on vitamin C in dehydrated pickled/candied pineapples and guava - Mohamed, Suhaila; Kyi, Khin Ma Ma; Mat Sharif, Zainon (John Wiley & Sons, 1993)
Dehydrated pickled/candied guava and pineapples pretreated with 0.24 g kg−1 cysteine hydrochloride (cys‐HCl) had increased ascorbic acid retention and reduced colour change during storage. Dehydrated pineapples pretreated with cys‐HCl had two to three times the ascorbic acid content of control or metabisulphite‐treated products. The rate of ascorbic acid loss for all products stored at room temperature were similar, showing that cys‐HCl was only protective towards ascorbic acid during the preparation and dehydration process. Candied dehydrated guava showed less colour change and higher ascorbic acid retention (about 57%) than pickled guava (ascorbic acid retention about 30%). Cys‐HCl was quite effective in reducing browning of candied pineapples but not pickled pineapples. Sensory evaluation showed that candied guava pretreated with 0.24 g kg−1 cys‐HCl was generally preferred over the other dehydrated guava products. Cys‐HCl‐treated candied pineapples had the best flavour compared with all other dehydrated pineapple products. Cys‐HCl appeared to favour conversion of glucose to fructose during storage of dehydrated pineapples.